CBMT-33. VISUALIZING THE METABOLISM OF GLIOBLASTOMA PATIENT-DERIVED ORTHOTOPIC XENOGRAFTS BY MASS SPECTROMETRY IMAGING. (11th November 2019) - Upendra Rao, Jyotsna; Gibson, Katherine; Hamm, Gregory; Wright, Alan; Fala, Maria; Mair, Richard; Tsyben, Anastasia; Goodwin, Richard; Brindle, Kevin
Abstract: INTRODUCTION. Glioblastoma multiforme (GBM) has a dismal prognosis, which has been attributed to extensive inter- and intra-tumoural heterogeneity. To investigate the metabolic heterogeneity of GBM, we employed desorption electrospray ionization (DESI) imaging on snap frozen samples of GBM patient-derived orthotopic xenografts (PDOX) in rat brains, following infusion of [U- 13 C]glucose. METHODS. Athymic nude rats (n=3) were infused with [U- 13 C]glucose (0.4 mg/g body weight bolus, 0.012 mg/g/min at 300 µL/h infusion [1]) for 40, 80 and 120 min, followed by cardiac puncture to measure blood [U- 13 C]glucose levels using 13 C NMR spectroscopy. A second set of rats (n=2) were implanted intracranially with patient-derived GBM cells. The presence of tumour was confirmed by T2 -weighted MRI. One animal was infused with [U- 13 C]glucose for 2 h, while another with [ 12 C]glucose. The brains were snap frozen in liquid nitrogen followed by analysis with DESI imaging in negative ion mode (35 µm resolution). RESULTS. After a 2 h infusion, 43% of the circulating glucose was 13 C labelled. Unsupervised spatial clustering of the MSI data resulted in segmentation of normal brain from tumour. Levels of [ 12 C and 13 C]glucose were high in the peri-tumoural region and low within the tumour. [ 12 C and 13 C]lactate showed the opposite distribution, indicating that the rate of glucose utilization within the tumour exceeded the rate of delivery. The peri-necrotic and peri-tumoural areas had higher levels of glutamate compared to the rest of the tumour. CONCLUSIONS. The results demonstrate that the PDOX is metabolically heterogeneous and differs from surrounding brain. While the tumour was predominately glycolytic, the presence of glutamate in peri-necrotic and peri-tumoral regions indicates the presence of increased TCA cycle activity. Comparison of MSI data with histological staining of brain sections should yield additional information about the relationship between the tumour and its microenvironment.